PEMANFAATAN GAMIFIKASI DALAM PEMBELAJARAN PENDIDIKAN ISLAM: MEMBANGUN MOTIVASI SISWA DALAM MENGHAFAL AL-QUR'AN - I.M. Fatimah Zahro (Istinbath, 2024)
This paper explores the use of gamification in Islamic education, particularly in motivating students to memorize the Qur'an. Memorizing the Qur'an is a central element in Islamic education, but students often face challenges due to monotonous learning methods. Gamification, the integration of game elements such as points, rewards, and challenges into non-game contexts, has been identified as a potential tool to increase motivation and engagement in the learning process. This study employs a systematic literature review (SLR) approach to evaluate existing research on gamification's application in Islamic education. The findings show that gamification significantly enhances students' intrinsic motivation and engagement, creating a more interactive and enjoyable learning environment. Several educational applications, such as "Quran Companion," have successfully integrated gamification to improve students' memorization progress. This research highlights the effectiveness of gamification in Islamic education and offers recommendations for future curriculum development to further enhance student learning outcomes.